Receiver's access fee for a single sender - Martin Gregor (Charles University in Prague, Institute of Economic Studies (IES), 2014)
We study a game in which a sender with verifiable private information has to pay an access fee that is announced by a receiver to be able to convey her message to the receiver. The setting is motivated by the literature of pay-and-lobby politics, which finds that politicians decide to schedule informative meetings with lobbyists on the basis of their campaign contributions. We solve the game for all timings, prior beliefs, and noise and valuation parameters. We identify the receiver's tradeoff between the amount of information and the amount of revenue. At the tradeoff, the receiver decides to not receive an informative signal from the sender. Whether 'burying one's head in the sand' increases or decreases welfare depends on the degree of the receiver's benevolence.
Keywords: C72; C78; D72; D83; 330; disclosure; persuasion; hard evidence; access fee; lobbying